Fertility preservation in pediatric healthcare: a review - Chen, Lin; Dong, Zirui; Chen, Xiaoyan (Frontiers in Endocrinology, 2023)
Survival rates for children and adolescents diagnosed with malignancy have been steadily increasing due to advances in oncology treatments. These treatments can have a toxic effect on the gonads. Currently, oocyte and sperm cryopreservation are recognized as well-established and successful strategies for fertility preservation for pubertal patients, while the use of gonadotropin-releasing hormone agonists for ovarian protection is controversial. For prepubertal girls, ovarian tissue cryopreservation is the sole option. However, the endocrinological and reproductive outcomes after ovarian tissue transplantation are highly heterogeneous. On the other hand, immature testicular tissue cryopreservation remains the only alternative for prepubertal boys, yet it is still experimental. Although there are several published guidelines for navigating fertility preservation for pediatric and adolescent patients as well as transgender populations, it is still restricted in clinical practice. This review aims to discuss the indications and clinical outcomes of fertility preservation. We also discuss the probably effective and efficient workflow to facilitate fertility preservation.